2013
DOI: 10.1177/1938640013489341
|View full text |Cite
|
Sign up to set email alerts
|

Atypical Presentation of Verrucous Carcinoma

Abstract: Therapeutic, Level IV.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
19
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 65 publications
(89 reference statements)
0
19
0
Order By: Relevance
“…Carcinoma cuniculatum is a rare, locally invasive squamous cell carcinoma with a low grade of malignancy [ 1 ]. It is rare with only about 100 cases reported so far, with the first report by Aird et al [ 1 ] in 1954 [ 4 ]. It occurs in older patients, with at average age at diagnosis of about 60 years, and with a higher prevalence in men as compared to women.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Carcinoma cuniculatum is a rare, locally invasive squamous cell carcinoma with a low grade of malignancy [ 1 ]. It is rare with only about 100 cases reported so far, with the first report by Aird et al [ 1 ] in 1954 [ 4 ]. It occurs in older patients, with at average age at diagnosis of about 60 years, and with a higher prevalence in men as compared to women.…”
Section: Discussionmentioning
confidence: 99%
“…After excision, reconstruction of the surgical wound is often a challenge because of the extent and location of the tumor. Primary, secondary, and delayed closure techniques, skin grafts, and flaps have been suggested for larger skin defects [ 4 , 6 ]. Other conservative therapeutic approaches, for example, electrodesiccation, cryotherapy, and laser ablation, are not always effective and often result in tumor recurrence [ 3 ].…”
Section: Discussionmentioning
confidence: 99%
“…One review found no recurrences in 5 cases of EC treated with MMS. 23 As MMS is a tissue-sparing technique, this is a valuable modality for sites of functional importance such as the feet. Herein, we review various reported EC treatment modalities and outcomes, with an emphasis on recurrence rates for WLE and MMS.…”
mentioning
confidence: 99%
“…Verrucous carcinoma is a rarely occurring, low-grade variant of squamous cell carcinoma, slow-growing verrucous and with minimal dysplasia. [ 1 ] The incidence of epithelioma cuniculatum is unknown, with a predominance for men in their fifth–sixth decades. [ 2 ] It occurs most commonly on the ball of the sole (53%), followed by the toes (21%) and heel (16%).…”
mentioning
confidence: 99%
“…Metastasis from CC is rare, although it can invade deep into the soft tissues and can extend to tendons, muscles, or bone. [ 1 4 ] We report a case of a 67-year-old healthy man with 10 years history of enlarging cauliflower-like lesion of his right heel, initially diagnosed and treated as a wart. During the years, the lesion has grown progressively despite treatment until becoming a deeply penetrating mass, 6 cm × 5 cm × 3 cm, with an exophytic and hyperkeratotic component [ Figure 1a ].…”
mentioning
confidence: 99%